Analisa Kebijakan Dividen Berdasarkan Teori Lintner - Ratna Damayanti; Fithri Setya Marwati; Rochmi Widayanti (Agregat: Jurnal Ekonomi dan Bisnis, 2017)
Dividends are important to the company as they relate to the allocation of revenues from corporate growth and wealth to shareholders. The purpose of this study is to analyze dividend policy proposed by Lintner stating that dividend policy is influenced by profitability and lagged dividend. The population of this study are companies listed on the Indonesia Stock Exchange in 2012-2015. Samples taken as many as 133 companies. The sampling technique used purposive sampling technique. The analytical method used is multiple linear regression. The result of the research concludes that profitability and lagged dividend have significant positive influence to dividend policy.